A joint view on genetic variants for adiposity differentiates subtypes with distinct metabolic implications - Thomas W Winkler (Nature Portfolio, 2018)
In GWAS, waist-to-hip ratio (WHR) is often adjusted for body mass index (BMI) to account for their correlation (WHRadjBMI). Here, Winkler et al. classify 159 genetic variants for BMI, WHR, or WHRadjBMI based on their effect directions for BMI and WHR to differentiate subtypes of adiposity genetics.